Anastatica Hierochuntica L. Used As an Alternative of Conjugated Estrogen (Premarin) in Rabbit Females (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
There are risks and benefits with all medicines and estrogen replacement is no exception. In fact, estrogen replacement is one of the most controversial topics in Endocrinology. Anastatica hierochuntica L. is a popular treatment  for the management of female reproductive disorders. The present research highlights the effect of  aqueous extract of plant against conjugated estrogen(Premarin) in rabbits. Femal oryciolagus cuniculus rabbits were divided into four groups: the 1 st group, rabbits were orally administered  (using a feeding solution )with daily dose(5 mL distilled water)for two months, the 2nd group, the rabbits were treated with conjugated estrogen (50 µg/kg b.w, body weight )for one month. The 3rd  group, the rabbits were treated with aqueose extract of plant(100mg/mL) for one month and group 4th the rabbits were treated with aqueous extract of plant(100mg/mL) for two  months  . The level of estrogen evaluated in blood. The findings of the study indicated that the administration of conjugated estrogen (50µg/kg b. w) induced a significant increase in estrogen. The result suggests that aqueous extract of Anastatica hierochuntica L. may increased leve of estrogen.